Relevansi QS. Adz-Dzariyat: 56 dan Hadis Akhlak terhadap Penguatan Profil Pelajar Pancasila dalam Kurikulum Merdeka - Cinta Aprilia Putri; Aisyah Rizki Ramadhani; M. Ikhwanul Khoir; Ahmad Yusam Thobroni (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Character education is a central component of the Merdeka Curriculum, particularly through strengthening the Profile of Faith, Piety to God Almighty, and Noble Character. However, its implementation often emphasizes practical programs without sufficient theological grounding. This study analyzes the relevance of QS. Adz-Dzariyat: 56 and the Prophet’s hadith on the perfection of morals (Musnad Ahmad) to strengthening this profile in the Merdeka Curriculum. Using a library research method with normative-theological and pedagogical approaches, data were analyzed through content analysis of the Qur’an, hadith, classical and contemporary tafsir, curriculum documents, and relevant literature. The findings indicate that QS. Adz-Dzariyat: 56 establishes worship as the fundamental purpose of human existence, while the hadith positions noble character as the primary outcome of Islamic education. These values are consistent with the Merdeka Curriculum’s emphasis on faith, piety, and moral character, providing a theological foundation for strengthening character education through contextual and value-oriented learning.